A comprehensive review of hydrogen production from methanol thermochemical conversion for sustainability. (15th February 2021) - Garcia, Gabriel; Arriola, Emmanuel; Chen, Wei-Hsin; De Luna, Mark Daniel
Abstract: Methanol, a liquid hydrogen carrier, can produce high purity hydrogen when required. This review discusses and compares current mainstream production pathways of hydrogen from methanol. Recent research efforts in methanol steam reforming, partial oxidation, autothermal reforming, and methanol decomposition are addressed. Particular attention is paid to catalyst development and reactor technology. Copper-based catalysts are popular due to their high activity and selectivity towards CO2 over CO but are easily deactivated and have low stability. Attempts have been made using different metals like zinc, zirconia, ceria, chromium, and other transition metals. Catalysts with spinel structures can significantly improve activity and performance. Palladium-zinc alloy catalysts also have high selectivity towards H2 and CO2 . For reactors, novel structures such as porous copper fiber sintered-felt are prefabricated and pre-coated before employment in microreactors. Monolith structures provide maximum surface area for catalyst coatings and lower pressure drops. Membrane reactors drive reactions forward to produce more H2 . Swiss-roll reactors achieve heat recovery and energy saving in reactions. In summary, this comprehensive review of hydrogen production from methanol is conducive to the prospective development of a hydrogen-methanol economy. Graphical abstract: Image 1 Highlights: Four main hydrogen production processes from methanol are reviewed. Reaction mechanisms for methanol thermochemical conversion are discussed. Recent progress in catalyst and reactor developments is reported. A qualitative comparison between the processes is addressed. Perspectives and challenges for hydrogen production from methanol are underlined.